Drawing a “Geopolitics” of Medieval Middle East: Political Alliance and Rivalry among Islamic Caliphates, the Mongols, and the European Kingdoms - Karim, Muhammad Abdul (Al-Jami'ah Research Centre, 2023)
This article aims to sketch the “geopolitics” of the past by investigating the context of the medieval Islamic world. Not only in today’s world, international political and economic relations have also had their precedents in the past. Given its strategic position in this issue, the Middle East is one of the regions that are interesting to study in the context of geopolitical narratives from the past to the present. This article tries to unravel the geopolitical situation of the Medieval Middle East by tracing historical records related to the economic-political relations of Islamic dynasties through a broader picture by looking at their relationship with other political powers that existed at that time, especially the Mongols and European-Christian kingdoms in general. This exploration shows how the issues of political pragmatism filled with negotiations and the necessity of religious issues have been deeply intertwined with each other and became a major feature of geopolitical relations in the medieval Middle East.[Artikel ini menggambarkan sebuah sketsa tentang “geo-politik” di masa lalu dengan menginvestigasi konteks dunia Islam pada abad pertengahan. Tidak hanya terjadi di dunia saat ini, relasi internasional dalam bidang politik dan ekonomi juga telah memiliki presedennya di masa lalu. Timur tengah adalah salah satu ranah yang layak untuk dikaji dalam konteks narasi geopolitik sejak masa lalu hingga saat ini, mengingat posisinya yang strategis dalam isu ini. Artikel ini mencoba mengurai situasi geopolitik Timur Tengah pada abad pertengahan dengan menelusuri catatan sejarah terkait relasi ekonomi-politik dinasti-dinasti Islam ditinjau dari konteks yang lebih luas dengan melihat kaitannya dengan kekuaan politik lain yang ada ketika itu, termasuk Mongol dan kerajaan-kerajaan Kristen Eropa secara umum. Penelusuran ini menunjukkan bagaimana isu pragmatisme politik yang dipenuhi dengan negosiasi dan isu keagamaan telah sangat terkait satu sama lain dan menjadi fitur utama dalam relasi geopolitis di Timur Tengah pada abad pertengahan].